Culture’s Impact on Customer Motivation to Engage in Professional Service Enactments. - Schumann, Jan H; Wünderlich, Nancy; Zimmer, Marcus S (Schmalenbach Business Review)
Although professional service providers increasingly deliver their services globally, little is known about cross-cultural differences in customers’ motivation to participate in service production. To address this lacuna, we survey a total of 2,284 banking customers in 11 countries on their motivation to provide personal information to, and follow the advice of, their service providers. We find differences in both aspects, but only the differences in providing personal information can be explained by the cultural values of uncertainty avoidance, individualism/collectivism, and masculinity/femininity. To perform certain tasks in the service process, global professional service providers should acknowledge cultural differences in customers’ motivations.
Keywords: Co-Production; Culture; Customer Participation; Professional Services

System-level performance evaluation of reconfigurable processors - Enzler, Rolf; Plessl, Christian; Platzner, Marco (Microprocessors and Microsystems)
Reconfigurable architectures that tightly integrate a standard CPU core with a field-programmable hardware structure have recently been receiving impact of these design decisions on the overall system performance is a challenging task. In this paper, we first present a framework for the cycle-accurate performance evaluation of hybrid reconfigurable processors on the system level. Then, we discuss a reconfigurable processor for data-streaming applications, which attaches a coarse-grained reconfigurable unit to the coprocessor interface of a standard embedded CPU core. By means of a case study we evaluate the system-level impact of certain design features for the reconfigurable unit, such as multiple contexts, register replication, and hardware context scheduling. The results illustrate that a system-level evaluation framework is of paramount importance for studying the architectural trade-offs and optimizing design parameters for reconfigurable processors.
Keywords: FPGA; reconfigurable computing; co-simulation; Zippy

A UML Virtual Machine for Embedded Systems - Schattkowsky, Tim; Müller, Wolfgang (Proceedings of ISNG 05)
StateCharts are well accepted for embedded systems specification for various applications. However, for the specification of complex systems they have several limitations. In this article, we present a novel approach to efficiently execute an UML 2.0 subset for embedded real- time systems implementation with focus on hardware interrupts, software exceptions, and timeouts. We introduce a UML Virtual Machine, which directly executes sequence diagrams, which are embedded into hierarchically structured state transition diagrams. Whereas state diagrams are directly executed as Embedded State Machines (ESMs), sequence diagrams are translated into UVM Bytecode. The final UVM execution is performed by the interaction of the ESM and the Bytecode Interpreter. Due to our completely model- based approach, the UVM runtime kernel is easily adaptable and scalable to different scheduling and memory management strategies.
Keywords: UML; Executable Models; Hardware/Software Co-design; Virtual Machine; Embedded Systems

Co-simulation of a Hybrid Multi-Context Architecture - Enzler, Rolf; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))
Reconfigurable computing architectures aim to dynamically adapt their hardware to the application at hand. As research shows, the time it takes to reconfigure the hardware forms an overhead that can significantly impair the benefits of hardware customization. Multi-context devices are one promising approach to overcome the limitations posed by long reconfiguration times. In contrast to more traditional reconfigurable architectures, multi-context devices hold several configurations on-chip. On demand, the device can quickly switch to another context. In this paper we present a co-simulation environment to investigate design trade-offs for hybrid multi-context architectures. Our architectural model comprises a reconfigurable unit closely coupled to a CPU core. As a case study, we discuss the implementation of a FIR filter partitioned into several contexts. We outline the mapping process and present simulation results for single- and multi-context reconfigurable units coupled with both embedded and high-end CPUs.
Keywords: Zippy; co-simulation

Hardware/Software Codesign in Speech Compression Applications - Plessl, Christian; Maurer, Simon
Keywords: co-design; speech processing